2018
DOI: 10.1017/jfm.2018.324
|View full text |Cite
|
Sign up to set email alerts
|

The structure and origin of confined Holmboe waves

Abstract: Finite-amplitude manifestations of stratified shear flow instabilities and their spatio-temporal coherent structures are believed to play an important role in turbulent geophysical flows. Such shear flows commonly have layers separated by sharp density interfaces, and are therefore susceptible to the so-called Holmboe instability, and its finite-amplitude manifestation, the Holmboe wave. In this paper, we describe and elucidate the origin of an apparently previously unreported long-lived coherent structure in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
103
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(110 citation statements)
references
References 51 publications
(59 reference statements)
6
103
0
Order By: Relevance
“…The question then arises as to how these mechanisms compete, and also how turbulence is deformed by stratification in more generic situations. Just to mention one example, it has recently been observed that horizontal confinement in a duct, and hence the inevitable introduction of spanwise shear to the Holmboe instability of a principally vertically sheared (relatively 'sharp') density interface gives rise to a new robust long-lived nonlinear coherent structure in the form of a 'confined Holmboe wave' (Lefauve et al 2018). It remains to be seen how similar confinement might affect turbulent flows, even without the sharp density interface typically required for the initial occurence of Holmboe-type instabilities.…”
Section: Discussionmentioning
confidence: 99%
“…The question then arises as to how these mechanisms compete, and also how turbulence is deformed by stratification in more generic situations. Just to mention one example, it has recently been observed that horizontal confinement in a duct, and hence the inevitable introduction of spanwise shear to the Holmboe instability of a principally vertically sheared (relatively 'sharp') density interface gives rise to a new robust long-lived nonlinear coherent structure in the form of a 'confined Holmboe wave' (Lefauve et al 2018). It remains to be seen how similar confinement might affect turbulent flows, even without the sharp density interface typically required for the initial occurence of Holmboe-type instabilities.…”
Section: Discussionmentioning
confidence: 99%
“…ML14 correctly recognised that the two-layer exchange flow was maximal because it is hydraulically controlled at both ends of the duct where it meets the reservoirs through a sharp change in geometry (an idea already present in Wilkinson (1986)). In other words, the flow is subcritical with respect to long interfacial waves inside the duct, and critical at either end, preventing the propagation of information (in particular of the exchange flow rate) from the exterior into the duct (see ML14, Lefauve et al 2018, § 3, and Lefauve 2018, § 1.3.2 for more details). The exchange flow is sustained in a quasi-steady state until the controls are 'flooded' by the accumulation of fluid of a different density coming from the other reservoir.…”
Section: Measurement Volumementioning
confidence: 99%
“…Gravity acts in the negative z-direction. The setup, which is inspired by different experimental configurations (see, for example, Simpson and Linden 1989;Meyer and Linden 2014;Lefauve et al 2018), consists of two reservoirs connected by a channel of height h and length L, with L h (implicitly assuming that end effects at x = ±L/2 can be ignored). Each reservoir contains water with a different initial salt concentration, denoted by the salinities s 1 and s 2 in the left and right reservoirs, respectively.…”
Section: Numerical Setupmentioning
confidence: 99%